'A Quarrel of Limited Concern to the People of this Country'?: The British Labour Movement and Chile Solidarity. Issue 3 (December 2016) - Hirsch, Shirin
Abstract : This article explores different examples of British trade union solidarity with Chile; moments of internationalist action which have been very little researched. It uses these moments to examine the British labour movement in the 1970s and argues that national politics was central to this contested internationalist activity. The article draws out the identification with Chilean workers felt by a certain layer of the British labour movement in this period, expressed through the 'blackings' in East Kilbride. In contrast, the limitations of this identification are illuminated through the ITT occupation where instead by happenstance the workers stumbled across the history of the Chilean coup.